Tattoo-associated uveitis - Mak, C Y; Ho, M; Chan, A Z; Iu, L P L; Cheung, C M T; Brelen, M E; Choi, P C L; Young, A L (Hong Kong medical journal = Xianggang yi xue za zhi, 2021)
Systemic sarcoidosis, a rare disease in Asians, can occasionally cause tattoo granuloma and uveitis.1 Tattoo-associated uveitis without systemic sarcoidosis is a rare entity first described in a case series half a century ago.2 The disease is characterised by recurrent episodes of uveitis in conjunction with raised and indurated tattoo, while histology of affected skin demonstrates florid non-caseating granulomatous reaction indistinguishable from tattoo granuloma in systemic sarcoidosis.3 The exact pathogenesis is unknown, but it was believed to be a type of delayed hypersensitivity reaction to tattoo pigments.3 Treatment is mainly to control ocular inflammation by topical and systemic steroid, with or without steroid-sparing agent. Analysis or interpretation of data: CY Mak, M Ho, LPL Iu, PCL Choi. CY Mak 1; Mary Ho 1; Angela Z Chan 2; Lawrence PL Iu 1; Christina MT Cheung 3; Marten E Brelen 1; Paul CL Choi 2; Alvin L Young 1 1 Department of Ophthalmology and Visual Sciences, Prince of Wales Hospital, Hong Kong 2 Department of Anatomical and Cellular Pathology, Prince of Wales Hospital, Hong Kong 3 Division of Dermatology, Department of Medicine and Therapeutics, Prince of Wales Hospital, Hong Kong